THE BIOLOGICAL ACTIVITIES OF MOLTKIA AUREA BOISS., AN ENDEMIC SPECIES TO TURKEY - Balpinar, Neslihan; Okmen, Gulten (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Staphylococcus aureus is the direct reason of mastitis. Mastitis is a disease characterized by pathological changes in mammary glands as well as physical, chemical, bacteriological changes in milk. This disease causes loses in milk yield and quality. In recent years, it is reported that mastitis pathogens have developed a resistance to antibiotics as a natural consequence of widespread use of it. Today’s researches are focused on discovering and using new antibiotics against bacteria. The aim of this paper is to examine the antibacterial properties of Moltkia aurea Boiss.][o] (an endemic species to Turkey), and its other biological activities. Materials and Methods: All of the extracts were tested by disc diffusion assay in order to screen antibacterial activity. MIC values were evaluated as antibacterial activities of plant extracts. The non-enzymatic antioxidative activities including DPPH radical scavenging effects were studied in vitro. Results and Conclusions: Results shown that the extracts had strong antibacterial effects on three bacteria (S. aureus- 17, S. aureus-18 and CNS-37) and the range of inhibition zone was 4-6mm. This three bacteria screened the lowest sensitivity to 65000 μg /mL concentration. Besides, the extracts were tested for non-enzymatic antioxidant activities. As a result, the methanol extract of the flower displayed a strong antioxidant activity. The various extracts of Moltkia aurea have different antibacterial and antioxidant properties.